Changing tastes on the linguistic landscape of Asmara, Eritrea. (13th April 2019) - Weldemichael, Tedros; Peck, Amiena; Williams, Quentin
Abstract : Asmara, the capital city of Eritrea, has for the longest time had a clear demarcation between Christian and Muslim eateries, with Arabic as the differentiating marker between the two. With the inﬂux of Sudanese Muslim tourists, however, a number of Christian eateries in downtown Asmara have begun including Arabic on their signage. We approach the changes to the LL in two ways: (i) through a geosemiotic analysis of selected mixed signs on and around Asmara's busy downtown Harnet Avenue, and (ii) through a discourse analysis of interviews with Christian establishment owners/managers. We contend that by viewing the versatility of Arabic as an 'adaptable artefact' (cf. Pennycook, 2017) in Asmara, we can moreover discuss the LL as semiotic assemblages of 'halaalness' which caters to the visceral needs for comfort at the eateries under study. Here we follow Pennycook (2017) and Bennet (2010) who contend that language and, similarly, linguistic repertoires should not be conﬁned to individuals per se as space and practices can also be said to express themselves multilingually through artifact, bodies and semiotics.